Breaking the Law of Valgus: the surprising and unexplained prevalence of medial patellofemoral cartilage damage. Issue 11 (25th April 2012) - Gross, K Douglas; Niu, Jingbo; Stefanik, Joshua J; Guermazi, Ali; Roemer, Frank W; Sharma, Leena; Nevitt, Michael C; Segal, Neil A; Lewis, Cora E; Felson, David T
Abstract : Objectives: To compare the prevalence of medial and lateral patellofemoral (PF) cartilage damage in three large osteoarthritis (OA) studies and determine the relationship of this damage to varus, neutral and valgus knee alignment. Methods: In the Boston OA of the Knee, Framingham OA and Multicenter OA studies, MRIs were read for cartilage morphology at the medial and lateral patella and trochlea femoris using Whole-Organ MRI Scores (WORMS). WORMS scores ≥2 (any cartilage defect), ≥3 (areas of partial thickness loss), ≥4 (diffuse partial thickness loss) and ≥5 (extensive full thickness loss) were all variously considered as thresholds to identify damage that may indicate OA. Full-limb radiographs were measured for mechanical alignment, and varus (<−2°), neutral (-2° to 2°) and valgus (>2°) knees were identified. Results: The prevalence of medial PF cartilage damage exceeded that of lateral damage in all three studies and according to nearly every threshold. Only among severely involved knees (WORMS ≥4 or ≥5) did the prevalence of lateral PF cartilage damage approximate that of medial damage. The high prevalence of medial PF damage persisted in all strata of knee alignment. Even among knees with valgus alignment, the prevalence of lateral PF cartilage damage equalled or surpassed that of medial PF damage only when the threshold was specific to severely involved knees. Conclusions: Medial PF cartilage damage is at least as prevalent within these older adult populations as lateral PF cartilage damage.